2011
DOI: 10.4236/cm.2011.24021
|View full text |Cite
|
Sign up to set email alerts
|

Bitter Melon (Momordica Charantia) Reduces Serum Sialic Acid in Type2 Diabetics: Evidence to Delay the Process of Atherosclerosis

Abstract: More than 1000 herbal products have been used by diverse cultures of the world to treat hyperglycemia and among them bitter melon (Momordica charantia) is one of the most popular herbal resource. The beneficial effects of bitter melon is not limited to hypoglycaemia only, but it also ameliorates diet induced obesity, insulin resistance and exhibit cardioprotective effects. The present study attempts to investigate the effect of bitter melon fruit juice on a newly investigated risk factor, sialic acid in type2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…More than 1 000 herbal products have been used by diverse cultures of the world to treat hyperglycemia and among them bitter melon (M. charantia) is one of the most popular herbal resource [101] . An earlier study on the development of diabetic cataracts demonstrated that blood sugar level-dependent cataract formation w a s s l o w e d d o w n b y t h e c o n s u m p t i o n o f b i t t e r gourd fruit extract in association with better glucose homeostasis [102] .…”
Section: Clinical Studies Of M Charantiamentioning
confidence: 99%
“…More than 1 000 herbal products have been used by diverse cultures of the world to treat hyperglycemia and among them bitter melon (M. charantia) is one of the most popular herbal resource [101] . An earlier study on the development of diabetic cataracts demonstrated that blood sugar level-dependent cataract formation w a s s l o w e d d o w n b y t h e c o n s u m p t i o n o f b i t t e r gourd fruit extract in association with better glucose homeostasis [102] .…”
Section: Clinical Studies Of M Charantiamentioning
confidence: 99%
“…This previous study found that administration of extract was effective to lowering FPG, HbA1C and serum Sialic Acid (SSA) as well. This study did not find the effectiveness of lowering total cholesterol, HDL-cholesterol, LDL-cholesterol [13][14][15] . Our recent study did not perform the effect of extract to HbA1C level and SSA because the study was only conducted in a month, that would effect no differences on such parameters.…”
Section: Discussionmentioning
confidence: 60%
“…This supports the findings of Tannin-spitzet al, Bernard et al report that cucurbitacin glycosides are having good antioxidant activity. 26,27 Catecholamines are important regulators of myocardial contractility and metabolism. However, it has been known for a long time that excess catecholamines are responsible for cellular damage, observed in clinical conditions like angina, transient myocardial hypoxia, acute coronary insufficiency and subendocardial infarct.…”
Section: Discussionmentioning
confidence: 99%